A docking-based structural analysis of geldanamycin-derived inhibitor binding to human or Leishmania Hsp90 - Palma, Luana Carneiro (Sci Rep, 2019)
Leishmaniasis is a neglected disease that affects millions of individuals around the world. Regardless of clinical form, treatment is based primarily on the use of pentavalent antimonials. However, such treatments are prolonged and present intense side effects, which lead to patient abandonment in many cases. The search for chemotherapeutic alternatives has become a priority. Heat Shock Protein 90 (Hsp90) inhibitors have recently come under investigation due to antiparasitic activity in Plasmodium sp., Trypanosoma sp. and Leishmania sp. Some of these inhibitors, such as geldanamycin and its analogs, 17-AAG and 17-DMAG, bind directly to Hsp90, thereby inhibiting its activity. Previous studies have demonstrated that different parasite species are more susceptible to some of these inhibitors than host cells. We hypothesized that this increased susceptibility may be due to differences in binding of Hsp90 inhibitors to Leishmania protein compared to host protein. Based on the results of the in silico approach used in the present study, we propose that geldanamycin, 17-AAG and 17-DMAG present an increased tendency to bind to the N-terminal domain of Leishmania amazonensis Hsp83 in comparison to human Hsp90. This could be partially explained by differences in intermolecular interactions between each of these inhibitors and Hsp83 or Hsp90. The present findings demonstrate potential for the use of these inhibitors in the context of anti-Leishmania therapy.